NAN--a national voice for community-based services to persons with AIDS. - Kawata, P A (1988)
Because of the variety of needs engendered by AIDS, a broadbased response to the epidemic is warranted. The traditional medical model, with its emphasis on inpatient hospital care, is expensive and fails to address other needs of people with AIDS (PWAs). This paper outlines an alternative model: the community-based response, or continuum-of-care model. It builds on earlier community models of an integrated network of service providers who can better meet a range of needs of PWAs outside the hospital. Although the model may include a designated hospital AIDS unit that supplies inpatient services, the continuum-of-care model incorporates other nonacute and psychosocial services offered through community-based providers, and these services rely to a large extent on volunteers. Nationwide, more than 400 community-based AIDS service organizations have been formed in response to the growing AIDS epidemic, or have evolved from existing organizations. The National AIDS Network (NAN) was formed in 1985 by five such organizations to represent at the national level the vision of community-based AIDS care. As the nexus for a national community-based response, NAN acts as a conduit for service providers to share experience as well as a clearinghouse for information and programs.